2022
DOI: 10.1371/journal.ppat.1010784
|View full text |Cite
|
Sign up to set email alerts
|

Many ways, one microorganism: Several approaches to study Malassezia in interactions with model hosts

Abstract: Malassezia, a lipophilic and lipid-dependent yeast, is a microorganism of current interest to mycobiologists because of its role as a commensal or pathogen in health conditions such as dermatological diseases, fungemia, and, as discovered recently, cancer and certain neurological disorders. Various novel approaches in the study of Malassezia have led to increased knowledge of the cellular and molecular mechanisms of this yeast. However, additional efforts are needed for more comprehensive understanding of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…The emergence of drug-resistant microorganisms has increased exponentially despite the discovery of new therapeutic antibiotics [35][36][37][38][39][40]. Identifying new phytopreparations that can destroy single planktonic cells and microbial communities in biofilms, thereby preventing antibiotic resistance, an important development [13,[41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of drug-resistant microorganisms has increased exponentially despite the discovery of new therapeutic antibiotics [35][36][37][38][39][40]. Identifying new phytopreparations that can destroy single planktonic cells and microbial communities in biofilms, thereby preventing antibiotic resistance, an important development [13,[41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Other species are related to fungemia, and recently, some authors have suggested an association of fungemia with Crohn’s disease [ 8 ] and Parkinson’s disease [ 9 ]. Furthermore, to try to understand why these yeasts transition from beneficial to opportunistic behavior, different approaches using in vitro or in vivo experimental models have been performed through several methodologies, such as omics tools, to elucidate the interaction between Malassezia and its host; these studies have been recently summarized [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In medical practice, this type of skin pathology is diagnosed based on the patient's clinical characteristics, and empirical management is given, so etiological isolation is not generally performed. It is important to highlight that these treatments require prolonged use of antifungal agents, which in turn takes the risk of leading to antifungal resistance development (13)(14)(15). Resistance mechanisms are not fully elucidated.…”
mentioning
confidence: 99%